The Economic Crisis and American Society - Castells, Manuel (Book collections on Project MUSE., 2014)
Taking a hard look at the crisis afflicting Western economies in recent years, Manuel Castells suggests that the very structures that fostered economic growth since 1945 are the same structures that are now undermining these economics. Pinpointing the new forms of the capitalist mode of production and the contradictory nature of its class relations as the root of the problem, he offers a comprehensive critique of American society and its economy. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available p.